2022
DOI: 10.3390/nu14091826
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Iodine Intake and Neurodevelopment of Offspring: The Japan Environment and Children’s Study

Abstract: Inadequate maternal iodine intake affects thyroid function and may impair fetal brain development. This study investigated the association between maternal iodine intake during pregnancy and neurodevelopmental delay in offspring at 1 and 3 years of age using a nationwide birth cohort: the Japan Environment and Children’s Study. We assessed dietary iodine intake during pregnancy using a food frequency questionnaire and child neurodevelopment using the Japanese translation of the Ages and Stages Questionnaire, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
0
9
1
Order By: Relevance
“…So that better iodine status contributes to improving thinking skills and agility in learning subjects at school. However, this is not in line with the research in school children aged 6-10 years that iodine status is not significantly related to cognitive school children (Hisada et al, 2022).…”
Section: Volcontrasting
confidence: 92%
“…So that better iodine status contributes to improving thinking skills and agility in learning subjects at school. However, this is not in line with the research in school children aged 6-10 years that iodine status is not significantly related to cognitive school children (Hisada et al, 2022).…”
Section: Volcontrasting
confidence: 92%
“…In most regions, habitual diets provide a low normal iodine supply and are more prone to induce iodine deficiency than excess [ 52 ]. Nevertheless, people living in some regions could be exposed to extraordinary iodine overload due to their diet.…”
Section: Iodine Excessmentioning
confidence: 99%
“…A 2017 Norwegian observational study in a MMID population found that low iodine intake from diet was associated with offspring language delay, behavioral problems, and fine motor skills at age three, but MIS did not affect outcomes [12]. A 2022 observational study in Japan evaluated iodine intake through diet along with kelp and seaweed in a marginally iodine-sufficient population and found an increased risk for delay in communication, fine motor, and problem solving at 1 and 3 years of age in those with the lower quintile for intake compared with those with the highest [74]. However, an observational study in India did not find an association between maternal UIC and mental and motor development, although in an iodine-sufficient population [75].…”
Section: Iodine and Child Neurodevelopmental Outcomesmentioning
confidence: 99%